Interaksi Padatan dan Pembentukan Eutektik dalam Campuran Biner Gemfibrozil-Nikotinamida - Prihandini , Khairinna; Wisudyaningsih , Budipratiwi; Wicaksono, Yudi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Gemfibrozil is an antihyperlipidemic drug that effectively lowers cholesterol and triglyceride levels in the blood. However, it has limitations, primarily low solubility and compactibility. Objective: The objective of this study was to analyze the solid interactions in a binary mixture of gemfibrozil and nicotinamide, which is useful for modifying the physicochemical properties of gemfibrozil through the formation of multicomponent solids. Methods: The method employed for solid-state interaction analysis was differential scanning calorimetry (DSC), which involved constructing solid-liquid phase diagrams, accompanied by Fourier transform infrared spectroscopy (FTIR) analysis to identify any hydrogen bonding interactions between the components. Results: The results revealed that the gemfibrozil-nicotinamide binary mixture formed a solid-liquid phase diagram characterized by a V-type solid curve. A eutectic mixture was observed at a molar ratio of 8:2, with a eutectic melting point of 59.3 °C. FTIR analysis revealed no hydrogen bonding interactions between gemfibrozil and nicotinamide. Conclusion: It was concluded that gemfibrozil in the binary mixture system did not form a solid interaction with nicotinamide but was a eutectic mixture. These findings can be used to design strategies for improving the physicochemical properties of gemfibrozil through the formation of multicomponent solids.